2014
DOI: 10.36457/gizindo.v32i1.68
|View full text |Cite
|
Sign up to set email alerts
|

KEMATIAN IBU DI INDONESIA (Analisis Data Survei Demografi dan Kesehatan Indonesia Tahun 1994-2007)

Abstract: MATERNAL MORTALITY IN INDONESIA (AN ANALYSIS OF THE 1994-2007 IDHS DATA)Maternal mortality is one of the main indicators of a community's health status. It also reflects the performance of a country's health system. Almost 90 percents of maternal mortality can be prevented by, among others, maternal health care programs, nutrition improvement programs, family planning programs, and increasing women's education level. This paper has two objectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Menurut World Health Organization (WHO), AKI secara global mencapai 211 per 100.000 kelahiran hidup, sedangkan berdasarkan hasil survey Sensus Penduduk dalam Profil Kesehatan Ibu dan Anak pada tahun 2020, AKI di Indonesia sebesar 305 per 100.000 kelahiran hidup (Annisya and Utama, 2020). AKI di Indonesia dari tahun ke tahun mengalami penurunan, meskipun demikian angkanya masih jauh dari target Millenium Development Goals (MDGs).…”
Section: Pendahuluanunclassified
“…Menurut World Health Organization (WHO), AKI secara global mencapai 211 per 100.000 kelahiran hidup, sedangkan berdasarkan hasil survey Sensus Penduduk dalam Profil Kesehatan Ibu dan Anak pada tahun 2020, AKI di Indonesia sebesar 305 per 100.000 kelahiran hidup (Annisya and Utama, 2020). AKI di Indonesia dari tahun ke tahun mengalami penurunan, meskipun demikian angkanya masih jauh dari target Millenium Development Goals (MDGs).…”
Section: Pendahuluanunclassified
“…Indonesian Health Demography Survey in 2017 reported that prolonged labor occupied the highest rate of complication by 40%. In West Java it was reported that prolonged labor contributed as much as 0.5% of the causes of maternal death (Annisya, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the event of discussion at the Health Department of East Java Province in November ago, the data was alarming about a great problem related to maternal death in Indonesia, as shown in Fig. 1 [2].…”
Section: Introductionmentioning
confidence: 99%